Enhancing Islamic Educational Institutions Within Philanthrophic Attitude; The Way On Waqaf Role In Aceh - Ruslan Razali (Al-Fikrah, 2018)
Waqaf is one of the key success factors in financing the educational programs among Muslim people in the entire world. It has been identified with the fervent roles, especially to support Islamic education. Overwhelmingly, waqaf has widely been used in enhancing the educational development and student empowerment as part of communal solidarity and attitude among Islamic society. Meanwhile, this paper intent to examine the spirit of philanthropy among Muslim people in supporting the Islamic educational institutions based on the aspects on waqaf contribution. It is remarkable, the study showed how the waqaf system has been perceived as an significant factor, and whether the spirit of generosity among Muslim society towards the Islamic education is reflected through the waqaf tradition. Besides, the study also showed how the waqaf played the significant roles in supporting the Islamic traditional education in Islamic history, and become the important source for many Islamic organizations since waqaf properties are utilized for the purpose of facilitating and supporting the educational processes.